2022
DOI: 10.1002/ags3.12550
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram for predicting stones recurrence in patients with bile duct stones undergoing laparoscopic common bile duct exploration

Abstract: Background The recurrence of bile duct stones is a long‐term outcome for patients undergoing laparoscopic common bile duct exploration (LCBDE) that is worthy of attention. This study aimed to investigate long‐term risk factors for stones recurrence after LCBDE and develop a nomogram for predicting the risk. Methods The clinical data on consecutive patients with bile duct stones undergoing LCBDE at Shanghai Tenth People's Hospital between January 2014 and February 2019 with a follow‐up period longer than 2 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…Additionally, PC can achieve the same rate of postoperative bile leakage and stone clearance compared with TTD and avoid the disadvantages associated with TTD [ 18 , 19 ]. Exceptionally, our study demonstrated for the first time that primary closure would reduce the recurrence rate of bile duct stones and the T-tube is a potential factor that promotes stone formation [ 14 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, PC can achieve the same rate of postoperative bile leakage and stone clearance compared with TTD and avoid the disadvantages associated with TTD [ 18 , 19 ]. Exceptionally, our study demonstrated for the first time that primary closure would reduce the recurrence rate of bile duct stones and the T-tube is a potential factor that promotes stone formation [ 14 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The operative technique for LCBDE was as described previously, using the “four-port and six-step” approach under general anesthesia [ 14 , 15 ]. Briefly, after successfully dissecting Calot’s triangle, the cystic duct was isolated and clamped with an absorbable clip (Lapro-Clip; Tyco Healthcare, Covidien, Norwalk, Conn., USA), which prevented the gallbladder stones sliding into the CBD during the operation.…”
Section: Methodsmentioning
confidence: 99%